The Influence of Abdullah Bin Zubair’s Rebellion on Political Stability in Syria 675-692 AD - Prasetya, Restu Dimas; Rozi, Muhammad Bahrudin (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to reveal the influence of Abdullah bin Zubair’s rebellion against the Umayyad Caliphate on political stability in Levant (now Syria, Palestine, Jordan, and Lebanon). The method used is the historical research method. From this research, the data obtained, 1) The land of Syria became the power base of the Umayyad Dynasty, with Damascus as its political capital and Jerusalem as its spiritual capital, as well as being a strategic military base to fight Byzantium, 2) The spread of Abdullah bin Zubair’s rebellion to Syria, including Homs and Damascus, divided the tribes in Syria and stopped military operations against Byzantium, and was used by the Byzantine Empire to launch attacks using its proxy, the Jarajimah (Mardait) in Lebanon, 3) The Umayyad Dynasty, under the leadership of Abdul Malik bin Marwan, used full military force to crush Abdullah bin Zubair’s rebellion which led to the assassination of Abdullah bin Zubair in 692 AD.